Expression of the minor isoform pea ferredoxin in tobacco alters photosynthetic electron partitioning and enhances cyclic electron flow - Blanco, Nicolás Ernesto (2013)
Ferredoxins (Fds) are ferrosulfoproteins that function as low-potential electron carriers in plants. The Fd family is composed of several isoforms that share high sequence homology but differ in functional characteristics. In leaves, at least two isoforms conduct linear and cyclic photosynthetic electron transport around photosystem I, and mounting evidence suggests the existence of at least partial division of duties between these isoforms. To evaluate the contribution of different kinds of Fds to the control of electron ﬂuxes along the photosynthetic electron transport chain, we overexpressed a minor pea (Pisum sativum) Fd isoform (PsFd1) in tobacco (Nicotiana tabacum) plants. The transplastomic OeFd1 plants exhibited variegated leaves and retarded growth and developmental rates. Photosynthetic studies of these plants indicated a reduction in carbon dioxide assimilation rates, photosystem II photochemistry, and linear electron ﬂow. However, the plants showed an increase in nonphotochemical quenching, better control of excitation pressure at photosystem II, and no evidence of photoinhibition, implying a better dynamic regulation to remove excess energy from the photosynthetic electron transport chain. Finally, analysis of P700 redox status during illumination conﬁrmed that the minor pea Fd isoform promotes enhanced cyclic ﬂow around photosystem I. The two novel features of this work are: (1) that Fd levels achieved in transplastomic plants promote an alternative electron partitioning even under greenhouse light growth conditions, a situation that is exacerbated at higher light intensity measurements; and (2) that an alternative, minor Fd isoform has been overexpressed in plants, giving new evidence of labor division among Fd isoforms.